2017
DOI: 10.1371/journal.pone.0169444
|View full text |Cite
|
Sign up to set email alerts
|

HBeAg Seroconversion in HBeAg-Positive Chronic Hepatitis B Patients Receiving Long-Term Nucleos(t)ide Analog Treatment: A Systematic Review and Network Meta-Analysis

Abstract: BackgroundHBeAg seroconversion is an important intermediate outcome in HBeAg-positive chronic hepatitis B (CHB) patients. This study aimed to compare the effect of nucleos(t)ide analogs (NAs) on HBeAg seroconversion in treating CHB with lamivudine, adefovir, telbivudine, entecavir, and tenofovir.MethodsNetwork meta-analysis of NA treatment-induced HBeAg seroconversion after 1–2 years of treatment was performed. In addition, NA treatment-induced HBeAg seroconversion after 3–5 years of treatment was systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…In the present study, up to 31.94% and 26.39% of patients achieved HBeAg loss and seroconversion at the second year of LdT + ADV combination therapy, respectively. Evidence from a network meta‐analysis showed that LdT treatment, whether short term or long term, was associated with higher HBeAg seroconversion compared with the other NAs …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the present study, up to 31.94% and 26.39% of patients achieved HBeAg loss and seroconversion at the second year of LdT + ADV combination therapy, respectively. Evidence from a network meta‐analysis showed that LdT treatment, whether short term or long term, was associated with higher HBeAg seroconversion compared with the other NAs …”
Section: Discussionsupporting
confidence: 63%
“…Evidence from a network meta-analysis showed that LdT treatment, whether short term or long term, was associated with higher HBeAg seroconversion compared with the other NAs. 28 Considering the lower rates of HBeAg loss and seroconversion in the LAM + ADV and ETV + ADV groups in the present study, we speculated that the relatively high rate of HBeAg seroconversion in LdT + ADV may be related to the effect of LdT. The advantage of…”
Section: Discussionmentioning
confidence: 63%
“…Despite the long-term follow-up, HBeAg seroconversion rates were lower in the NAs group. This finding was also demonstrated by Xing et al (24) that in long-term treatment with potent NAs, HBeAg seroconversion with the therapy was lower compared with spontaneous HBeAg seroconversion rate (25). The latest study conducted by Marcellin et al (26) in 2017 showed remarkable results of Peg-IFN treatment in long-term follow-up of CHB patients (26).…”
Section: Pegylated-interferon Entecavir Tenofovir Disoproxilmentioning
confidence: 53%
“…Initially, nucleoside analogues had a low genetic barrier and were prone to resistance, but recently, the high genetic barrier agents, ETV, tenofovir fumarate and TAF are not only potent, 54 but also have low levels of resistance and are relatively safe 55 . In addition to their effectiveness in viral suppression, they are also able to achieve HBeAg seroconversion, 56 but the rates of HBsAg loss are low. However, a pooled estimate of their efficacy in achieving HBsAg loss has not been performed.…”
Section: Discussionmentioning
confidence: 99%